The Influence of Educational Service Quality on Public Satisfaction - Hikmat; Bambang Mardi Sentosa; Andri Kurniawan; Aries Denta Putra; .B Yudi Muhtadi (Indonesia Journal of Engineering and Education Technology (IJEET), 2026)
Educational service quality has become a strategic factor in improving public satisfaction, particularly as educational institutions are increasingly expected to provide accessible, responsive, and high-quality services that meet the evolving needs of stakeholders. Despite various educational reforms, disparities in service quality remain evident in many institutions, affecting users' perceptions and overall satisfaction. This study aims to examine the influence of educational service quality on public satisfaction. The research employed a quantitative explanatory design using a survey approach. Data were collected from service users, including students, parents, and members of the public, through structured questionnaires distributed using proportionate random sampling. Educational service quality was measured using five dimensions adapted from the SERVQUAL model, namely tangibility, reliability, responsiveness, assurance, and empathy, while public satisfaction was assessed through perceived service performance, expectation fulfillment, overall satisfaction, and willingness to continue using and recommending the services. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the reliability and validity of the measurement model and to test the proposed structural relationships.The findings reveal that educational service quality has a positive and statistically significant effect on public satisfaction. Improvements in the quality of educational services, particularly in service reliability, responsiveness, and assurance, substantially enhance users' satisfaction and strengthen their trust in educational institutions. Furthermore, high-quality educational services encourage positive perceptions of institutional performance, increase stakeholder loyalty, and foster continuous public engagement in educational development. The study also demonstrates that educational service quality serves as a critical determinant of public satisfaction by bridging institutional performance with stakeholder expectations. These findings underscore the importance of strengthening service quality management through continuous evaluation, staff competency development, user-oriented service innovation, and effective quality assurance systems. This research contributes to the literature on educational management by providing empirical evidence that improving educational service quality is an effective strategy for enhancing public satisfaction and supporting sustainable educational governance.